Phytochemical analysis, antioxidant activity and antimicrobial activity of Tetragonula biroi bee bread extracts against selected microorganisms Kristel Deane Faye E. Benusa; Rolly G. Fuentes, adviser. - Benusa, Kristel Deane Faye E.; Fuentes, Rolly G. (2024)
Stingless bee species Tetragonula biroi, locally known as "lukot," "kalulot," and "kiwot", is one of the indigenous bee species in the Philippines. Extensive studies have already been conducted on the medicinal properties of its honey, pollen and propolis. However, literature regarding on the biological potential of its bee bread remains understudied. Thus, the study aimed to determine the presence of phytochemicals in T.biroi bee bread methanolic extracts, and evaluate its total antioxidant capacity and antimicrobial properties. Phytochemicals such as alkaloids, flavonoids, glycosides, phenols, and tannins were found to be present in the extract. The total antioxidant capacity (TAC) of the crude methanolic extract of T. biroi bee bread was measured by phosphomolybdenum method and the findings revealed that the extracts have a TAC that measured up to 31.68±0.61 mg AAEs/g. In terms of its antimicrobial activity, the bee bread crude methanolic extracts (100 mg/mL and 150 mg/mL) exhibited antibacterial activity against Staphylococcus aureus and the obtained minimum inhibitory concentration (MIC) of the extracts were 50 mg/mL. On the other hand, none of the extracts were found effective against Escherichia coli and Aspergillus niger. Based on these findings, bee bread of T. biroi species possesses phytochemicals that contribute to the antioxidant activity and antimicrobial activity of T. biroi bee bread.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.